STUDY OF ACADEMIC SELF EFFICACY, SOCIAL SUPPORT AND LEARNING SELF-REGULATORY OF STUDENT GUIDANCE AND COUNSELING - Laila, Siti Nur; Wibowo, Agus (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
This study is correlation research, which aims to find the relationship between academic self-efficacy, social support and self-regulation in learning. Study participants are students of Guidance and Counseling. Measuring instrument used is the scale of academic self-efficacy, social support scale and the scale of self-regulation. Methods of data analysis using product moment correlation. The results of the study (1) the image of self-efficacy of students' academic middle category, social support parents of students that are in the low category, and regulation of student learning in middle category, (2) there is a relationship which significant between self-efficacy of academic regulations learning, there the relationship between social support parents with regulation of learning, and there is a mutual relationship between academic self-efficacy and parental support with regulation of student learning.